2018
DOI: 10.3390/polym10050472
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Flexible Polyurethane Foam Shrinkage for Bra Cup Moulding Process Control

Abstract: Nowadays, moulding technology has become a remarkable manufacturing process in the intimate apparel industry. Polyurethane (PU) foam sheets are used to mould three-dimensional (3D) seamless bra cups of various softness and shapes, which eliminate bulky seams and reduce production costs. However, it has been challenging to accurately and effectively control the moulding process and bra cup thickness. In this study, the theoretical mechanism of heat transfer and the thermal conductivity of PU foams are first exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In recent years, different techniques have been developed for manufacturing flexible [22,23] and rigid [24,25,26] PMs with closed, open, or mixed (partly open and partly closed) cells. Also, the effect of different reinforcements (particles, fibers, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, different techniques have been developed for manufacturing flexible [22,23] and rigid [24,25,26] PMs with closed, open, or mixed (partly open and partly closed) cells. Also, the effect of different reinforcements (particles, fibers, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…14 Therefore, the design of a suitable cup is vital to accomplish the personalized customization of the molded cup bra. 15,16 The conditions for the cup pressing process have been extensively studied. 17 In a related study, Yip and Ng 18 identified the optimal molding conditions for each spacer fabric by thermomechanical analysis (TMA).…”
mentioning
confidence: 99%
“…Wu et al. 19 optimized the bra cup molding process by employing the Levenberg–Marquardt non-linear least-squares algorithm. These studies provide the scientific explanation and theoretical foundation for the molding of the cups.…”
mentioning
confidence: 99%